TO COMPARE THE HAEMODYNAMIC EFFECTS OF MIDAZOLAM AND PROPOFOL WHEN USED AS CO-INDUCTION AGENT TO PROPOFOL AND PROPOFOL ALONE - Dr Shivata Sharma; Dr Guddi Devi; Dr Shazia Banoo; Dr Madhu Kapoor Chib (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Co-induction of anaesthesia, the rationalebehind it being the combination therapy using two or more different drugs with the intention of reaching the same therapeutic goal was heavily criticized for a long time. However, it is accepted today, with the aim of achieving more specific 'target' responses, while minimizing side effects.Aim: To compare the haemodynamic effects of midazolam and propofol when used as co-induction agent to propofol   and thereby to find out which of these combinations, provides more haemodynamic stability as compared to propofol alone.Methods: A profile 132 patients were divided into three groups Group A [n=41]: received only propofol for induction of anaesthesia. Group B [n=47]: received midazolam 0.03mg/kg prior to induction of anaesthesia with propofol and Group C [n=44]: received propofol 0.3mg/kg prior to induction of anaesthesia with propofol. The baseline hemodynamic parameters (mean arterial pressure, heart rate and spo2) were recorded. After that parameters were recorded at 1, 2 and 5minutes respectively.  Graphically the data was presented by bar and line diagrams. A P-value of less than 0.05 was considered statistically significant. All P-values were two tailed.Results: Results: The mean induction dose of propofol was 115.4±15.51 mg in Group A, 73.8±11.89mg in Group B and 81.4±15.34 mg in Group C. The difference was statistically significant with p value of < 0.001. There was statistically significant increase in heart rate from the baseline (P-value